Ocean kinetic energy and photosynthetic biomass are important drivers of planktonic foraminifera diversity in the Atlantic Ocean - Rufino, Marta M.; Salgueiro, Emilia; Voelker, Antje A. H. L.; Polito, Paulo S.; Cermeño, Pedro A.; Abrantes, Fatima (Frontiers in Marine Science, 2022)
To assess the anthropogenic effect on biodiversity, it is essential to understand the global diversity distribution of the major groups at the base of the food chain, ideally before global warming initiation (1850 Common Era CE). Since organisms in the plankton are highly interconnected and carbonate synthesizing species have a good preservation state in the Atlantic Ocean, the diversity distribution pattern of planktonic foraminifera from 1741 core-top surface sediment samples (expanded ForCenS database) provides a case study to comprehend centennial to decadal time-averaged diversity patterns at pre-1970 CE times, the tempo of the substantial increase in tropospheric warming. In this work, it is hypothesized and tested for the first time, that the large-scale diversity patterns of foraminifera communities are determined by sea surface temperature (SST, representing energy), Chl-a (a surrogate for photosynthetic biomass), and ocean kinetic energy (as EKE). Alpha diversity was estimated using species richness (S), Shannon Wiener index (H), and Simpson evenness (E), and mapped using geostatistical approaches. The three indices are significantly related to SST, Chl-a, and EKE (71-88% of the deviance in the generalized additive mixed model, including a spatial component). Beta diversity was studied through species turnover using gradient forest analysis (59% of the variation). The primary community thresholds of foraminifera species turnover were associated with 5-10 ºC and 22-28 ºC SST, 0.05-0.15 mg m-3 Chl-a, and 1.2-2.0 cm2 s-2 log10 EKE energy, respectively. Six of the most important foraminifera species identified for the environmental thresholds of beta diversity are also fundamental in transfer functions, further reinforcing the approaches used. Four major bioregions have been defined based on the results of beta diversity analysis, identifying the major marine latitudinal gradients, the most important upwelling areas (Benguela Current, Canary Current), the Equatorial divergence, and the subtropical fronts (Gulf Stream-North Atlantic Drift path in the north, and the South Atlantic current in the south). In conclusion, we provide statistical proof that energy (SST), food supply (Chl-a), and currents (EKE) are the main environmental drivers shaping planktonic foraminifera diversity in the Atlantic ocean and define the associated thresholds for species change on those variables.